2012
DOI: 10.5194/angeo-30-97-2012
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic structure and wave properties associated with sharp dipolarization front observed by Cluster

Abstract: Abstract. Multiple dipolarization fronts (DFs) were observed by Cluster spacecraft in the magnetotail during a substorm. These DFs were kinetic structures, embedded in the bursty plasma flow, and moved earthward (mainly) and dawnward. Intense electric field, parallel and perpendicular currents were detected in the DF layer. These front layers were energy dissipation region (load region) where the energy of electromagnetic fields were transferred to the plasma thermal and kinetic energy. This dissipation was do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
167
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(178 citation statements)
references
References 44 publications
11
167
0
Order By: Relevance
“…A number of case studies [Le Contel et al, 2009;Deng et al, 2010;Khotyaintsev et al, 2011;Huang et al, 2012] reported observations of whistlers in relation to DFs. In particular, they found whistlers in the magnetic flux pileup region (FPR), where the electron distribution has a perpendicular anisotropy, which is large enough to drive whistlers via the whistler anisotropy instability [Le Contel et al, 2009].…”
Section: Introductionmentioning
confidence: 99%
“…A number of case studies [Le Contel et al, 2009;Deng et al, 2010;Khotyaintsev et al, 2011;Huang et al, 2012] reported observations of whistlers in relation to DFs. In particular, they found whistlers in the magnetic flux pileup region (FPR), where the electron distribution has a perpendicular anisotropy, which is large enough to drive whistlers via the whistler anisotropy instability [Le Contel et al, 2009].…”
Section: Introductionmentioning
confidence: 99%
“…The term dipolarization front was first proposed by Nakamura et al [6] when studying the motion of a DF during a flow burst event and has since been studied extensively, both statistically [7,8] and in multicase analysis [9,10]. Observations have shown that DFs are earthward-propagating structures with thicknesses comparable to ion gyroradii and are usually associated with large amplitude transient electric fields [8,11,12], waves [13][14][15], and electric current systems [8,12,16].…”
Section: Introductionmentioning
confidence: 99%
“…Behind the fronts, active wave emissions in the whistler frequency range are observed (Deng et al 2010a,b;Hwang et al 2011a;Huang et al 2012;Hwang et al 2014a;Viberg et al 2014). Deng et al (2010b) and Huang et al (2012) attributed the generation of the whistler waves to the electron temperature anisotropy (T ⊥ > T || ) caused by the pileup of the magnetic field lines, similar to the whistlers observed in the downstream region of the reconnection jet (Fujimoto and Sydora 2008).…”
Section: Betatron and Stochastic Accelerationmentioning
confidence: 89%
“…These wave emissions often appear to be coincident with the magnetic field maxima, being possibly related to changes in electron gyromotion occasioned by the increased magnetic strength. Huang et al (2012) showed wave activity near the ion cyclotron frequency that arose from an Alfvén ion cyclotron instability driven by the cross-field ion drift in the front layer of a DF.…”
Section: Betatron and Stochastic Accelerationmentioning
confidence: 99%